Foreign direct investment in transitional economies :case study of China and Poland - Du Pont , Michael (London, 2000)
Foreign Direct Investment in Transitional Economies presents a detailed investigation into the recent changes in the patterns and determinants in inflows of FDI to transitional economies. The author re-evaluates conventional theories of FDI, and analyses the many changes taking place in the nature of international business, both in terms of the drives of the trans-border transactions, and the strategic orientation of the firms that engage in those transactions. This comparative investigation is based on original research detailing the experiences of FDI in the economies of China and Poland through case studies of over 200 multinationals, and takes into account the dynamic forces of globalization and their effects on FDI.
Keywords: "Investments,foreign-China-Case studies"